TRAUMATIC OCCLUSION: DEFINITION, CAUSES, DIAGNOSIS AND TREATMENT (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Traumatic occlusion is a condition in which the normal ratio of dentition is disrupted, which can lead to damage to teeth, gums and jaw joints. This phenomenon is of significant importance in dentistry, as it can cause a number of complications, including jaw pain, headaches, and chewing problems. In this article, we will consider the definition of traumatic occlusion, its causes, diagnostic methods and treatment approaches.